Analisis kelayakan usaha tani Kopi Arabika di Kabupaten Simalungun - Ulidesi Siadari; Heri Dia Anata Batubara; Pertama Yul Asmara Pane; Ade Maya Mei Shanty (LP2M Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to determine the feasibility of farming and analyze the sensitivity of Arabica coffee farming to the increase in costs and the decrease in the selling price of Arabica coffee in Simalungun Regency. The population of this study were Arabica coffee farmers, the number of respondents in this study was 60 people. The method used in the feasibility analysis is to calculate the R/C ratio, Return on Investment (ROI), NPV, IRR, Net B/C, and PP. Meanwhile, analyzing the sensitivity of farming is carried out using the method of increasing costs and decreasing the selling price of Arabica coffee in Simalungun Regency. Based on the feasibility analysis of the farming business carried out, Arabica coffee farming is categorized as still feasible to cultivate. Meanwhile, Arabica coffee farming is more sensitive to the decline in the selling price of Arabica coffee by 10% and 20%, respectively. The feasibility analysis and sensitivity analysis are one of the things that encourage people to continue cultivating Arabica coffee because based on the feasibility analysis and sensitivity analysis, Arabica coffee is suitable for cultivation.